Criminal Liability of Political Buzzers for Disseminating False Information on Social Media under Indonesia's 2026 Criminal Law Adjustments - James Simanjuntak; Muhammad Rifky Adamsyah (Jurnal Ilmu Hukum Kyadiren, 2027)
Political buzzers become a matter of criminal law when the amplification of political messages shifts into the dissemination of false news or notices through social media. This article examines the structure of the relevant offenses and the criminal liability of political buzzers after Indonesia's Criminal Code entered into force and was simultaneously adjusted by Law No. 1 of 2026 on Criminal Law Adjustments. Using prescriptive normative legal research, the study applies statutory, conceptual, and case approaches together with grammatical, systematic, teleological, and temporal interpretation. It finds that political buzzers do not constitute a special category of offender; liability turns on each person's conduct and culpability. For conduct committed before January 2, 2026, Article 28(3) in conjunction with Article 45A(3) of the EIT Law required intent, knowledge of falsity, electronic dissemination, and actual public unrest in physical space. Since January 2, 2026, Articles 263 and 264 of the Criminal Code, as adjusted by Law No. 1 of 2026, both require knowledge and actual public unrest, while differing in the type of prohibited content. Constitutional Court Decision No. 170/PUU-XXIV/2026 confirms their result-based character. The article proposes a six-layer test covering tempus delicti and lex mitior, attribution, content classification, mens rea, public unrest and causation, and modes of participation.